Personalized Ventilation System Modelling fora Metabolic-variant Manikin in an Asymmetrical Building Environment - Olofinkua, Joseph O.; Ogedengbe, O. B. (UNILAG Journal of Medicine, Science and Technology, 2019)
The computational stencil for the design ofpersonalized ventilation system (PVS) is developed,especially for a metabolic-variant manikin in a built environment. The asymmetric space within the 2001 campus cafeteria is simulated using a two-dimensional finite volume formulation.Withinthe fairly ventilated cafeteria, the kitchen space is adjacent to the customers sitting area where unsatisfactory thermal conditions from the kitchen induces thermal discomfort to customers. Combination of theexisting ventilation system and a thermal personalized ventilation system is proposed to create thermal satisfactionfor occupants close to kitchen area. Using the existing experimental data,the performance of a thermal personalized ventilation system in a 2.7m x 2.6m space with outlet vent dimension of 0.2m is investigated. Parametric studies of the different comfort zones with variations in outlet vents are undertaken. The predicted results enable the identification of the discomfort zone and provide useful information for the design of a personalized ventilation system. It is anticipated that a performance analysis of the variation in metabolic activities of the manikin and the vents within the built environment will enhance the design of an optimal ventilation system.